Relações interdisciplinares no Design Estratégico: o bem-estar do usuário do serviço de saúde - Fontoura, Raissa Schmitt (Universidade do Vale do Rio dos Sinos, 2020)
The expansion of design towards the strategic perspective of project thinking, with activities in organizations, communities and institutions of public and private interests, stimulated the involvement of people directly or indirectly linked to projects through a movement of cocreation. The bias of collaboration and collective views in moments of ideation and development of ideas emphasized the interdisciplinary aspect of design, which characterizes exchanges between the knowledge of different disciplines so that these points of view can complement each other and integrate ways of thinking and acting in design practices. In this study, it starts from the context of a design project that aims to enhance the wellbeing of children undergoing cancer treatment. From the perspective of subjective wellbeing worked on in the research, we sought to obtain perceptions from various angles of the service, including the interaction of designers and professionals from the Oncopediatrics unit of the institution where it was performed. In these interactions, interdisciplinary relationships arising from contact between specialist designers, represented by the project team, and non-specialist designers, here understood as participants in disciplines other than design, were observed. The objective of the study, therefore, was guided on how to facilitate such interdisciplinary interactions in design projects for wellbeing. Through an exploratory method, the research was divided into: Movement 1 - intended for immersion in the context for the understanding and preliminary analysis of interdisciplinary interactions - and Movement 2, referring to the exploration, through an experimental practice, of how to facilitate the exchange process between disciplines in the given context. Based on a thematic analysis of the observations and prototypes developed, the main points of the relationship between the specialist designers of the project and the non-specialist designers were discussed. Such themes were synthesized in learned lessons that aim to reflect about the knowledge acquired and list design opportunities to facilitate interdisciplinary exchanges in projects focused on wellbeing.
Keywords: Interação interdisciplinar; Design para o bem-estar; Cocriação; Interdisciplinary interaction; Design for well-being; Cocreation; ACCNPQ::Ciências Sociais Aplicadas::Desenho Industrial